2020
DOI: 10.1163/15685357-02303300
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Religion on the Effectiveness of Ecological Advertising

Abstract: Attitudes toward ecological consumption can trigger environmentally responsible intentions and behaviors. Understanding how ecological messages can influence attitudes is essential to mitigate climate change. This paper analyzes how religious affiliation (or lack of), can influence attitudes toward green advertising and explores the role of religious affiliation in the effectiveness of ecological messages. The findings indicate that religious affiliation has an influence on the degree of effectiveness of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Hence, understanding how messages can influence attitudes is essential to prompt environmentally responsible intentions. Besides, the findings from Martinez-Fiestas et al (2020) indicate that religious affiliation influences each message's degree of effectiveness.…”
Section: Religious Orientation and Attitude Toward Sustainable-related Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, understanding how messages can influence attitudes is essential to prompt environmentally responsible intentions. Besides, the findings from Martinez-Fiestas et al (2020) indicate that religious affiliation influences each message's degree of effectiveness.…”
Section: Religious Orientation and Attitude Toward Sustainable-related Behaviormentioning
confidence: 99%
“…There are increasing studies in religious and sustainable behavior in the last few years (Abdullah and Keshminder, 2020;Martinez-Fiestas et al, 2020;Suki and Suki, 2015). Hence, understanding how messages can influence attitudes is essential to prompt environmentally responsible intentions.…”
Section: Religious Orientation and Attitude Toward Sustainable-related Behaviormentioning
confidence: 99%
“…However, religious advertising for the environment is more appealing to religious consumers than to non-religious consumers (Angelidis & Ibrahim, 2004 ). Martinez-Fiestas ( 2020 ) found that atheist consumers were more likely to positively respond to ecological advertising with a ‘gain-framed message’ (i.e., a message that focuses on benefits), while Catholic consumers were more likely to respond to ecological advertising with a loss-framed message.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Shen et al ( 2020 ) found that creative advertisements can attract viewers’ attention and increase the amount of attention directed toward a message. Moreover, Martinez-Fiestas et al ( 2020 ) found that religious affiliation influences the degree of effectiveness of the advertising message. We propose the following hypothesis:…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%